Shopee PayLater in Contemporary Digital Commerce: An Analysis Based on Maslahah Mursalah among University Students - Saqofah Washillatul Rizqia; Daniel Walker (PT. Islamic Research Publisher, 2024)
This study examines the use of Shopee Pinjam, a digital lending service integrated into the Shopee marketplace, among students of UIN Fatmawati Sukarno Bengkulu through the perspective of maslahah mursalah. As one of the rapidly growing financial technology services in Indonesia, Shopee Pinjam offers quick access to funds, simplified application procedures, collateral-free borrowing, and flexible installment options. For university students, this service has emerged as an alternative source of short-term financing to address both urgent and routine financial needs. This research employs a qualitative field study approach, with data collected through in-depth interviews with eight student users of Shopee Pinjam. The findings reveal that students are primarily attracted to the service due to its accessibility, speed, minimal administrative requirements, and its ability to assist with educational expenses, accommodation costs, and daily living needs. From the perspective of maslahah mursalah, the utilization of Shopee Pinjam can be regarded as permissible insofar as it generates tangible benefits, facilitates the fulfillment of essential needs, and does not lead to greater harm, exploitation, or financial distress. The study argues that digital lending services may function as a practical and flexible financial instrument for students when used responsibly and within reasonable limits. Academically, this research contributes to the growing discourse on Islamic legal responses to financial technology (fintech) by contextualizing the concept of maslahah mursalah within contemporary digital lending practices. It further enriches the literature on Islamic economic law by providing empirical insights into how Muslim students negotiate financial necessity, technological convenience, and religious considerations in the digital economy era.